Cardioplegia in paediatric cardiac surgery: a systematic review of randomized controlled trials. (26th June 2018) - Drury, Nigel E; Yim, Ivan; Patel, Akshay J; Oswald, Nicola K; Chong, Cher-Rin; Stickley, John; Jones, Timothy J
Abstract: OBJECTIVES: Cardioplegia is the primary method for myocardial protection during cardiac surgery. We conducted a systematic review of randomized controlled trials of cardioplegia in children to evaluate the current evidence base. METHODS: We searched MEDLINE, CENTRAL and LILACS and manually screened retrieved references and systematic reviews to identify all randomized controlled trials comparing cardioplegia solutions or additives in children undergoing cardiac surgery published in any language; secondary publications and those reporting inseparable adult data were excluded. Two or more reviewers independently screened studies for eligibility and extracted data; the Cochrane Risk of Bias tool was used to assess for potential biases. RESULTS: We identified 26 trials randomizing 1596 children undergoing surgery; all were single-centre, Phase II trials, recruiting few patients (median 48, interquartile range 30–99). The most frequent comparison was blood versus crystalloid in 10 (38.5%) trials, and the most common end points were biomarkers of myocardial injury (17, 65.4%), inotrope requirements (15, 57.7%) and length of stay in the intensive care unit (11, 42.3%). However, the heterogeneity of patients, interventions and reported outcome measures prohibited meta-analysis. Overall risk of bias was high in 3 (11.5%) trials, unclear in 23 (88.5%) and low in none. CONCLUSIONS: The current literature on cardioplegia in children contains no late phase trials. The small size, inconsistent use of end points and low quality of reported trials provide a limited evidence base to inform practice. A core outcome set of clinically important, standardized, validated end points for assessing myocardial protection in children should be developed to facilitate the conduct of high-quality, multicentre trials. PROSPERO registration: CRD42017080205.